Pendampingan Usaha Bagi Tenaga Kerja Mandiri Pemula Di Kecamatan Binjai Utara, Sumatera Utara - Supriani Sidabalok; Misdawita Misdawita (Jurnal Pengabdian Masyarakat Akademisi, 2025)
The mentoring of Tenaga Kerja Mandiri Pemula (TKMP) program is a program initiated by Kementerian Ketenagakerjaan with the aim of increasing productivity for new entrepreneurs. This is due to the importance of entrepreneurial activities for employment and economic growth. The purpose of this community service activity is to provide mentoring for TKMP participants in developing their businesses, starting with establishing the right business mindset. In fact, many micro-entrepreneurs still run their businesses without planning, financial records, marketing strategies, and even lack business legality. Therefore, after receiving mentoring, the start-up business group has financial reports, Business Proposal, Marketing Strategy and having business legality in the form of a Business Identification Number (NIB). Mentoring activities were carried out for 26 new entrepreneurs spread across the North Binjai District, Binjai City, North Sumatra. Mentoring activities were carried out in a hybrid manner, namely online media with virtual meetings to align perceptions and deliver materials. In addition, mentoring was also carried out offline, namely mentors directly visited the TKMP business. At the end of the mentoring, the results obtained were 88% of TKMP were able to prepare financial reports in the form of cash flow reports, 65% succeeded in preparing a Proposal/Business plan, 77% were able to prepare a marketing strategy in the form of a Business Model Canvas and as many as 50% of TKMP finally had a NIB. The next target after participating in this mentoring program is expected to be TKMP can move up to the Advanced Independent Worker (TKML) level, which means the business they run increases in turnover and assets